Potential of Human Neural Stem Cell Transplantation to Treat Acute Subdural Hematoma. (1st September 2019) - Chieng, Lee Onn; Yokobori, Shoji; Spurlock, Markus; Gajavelli, Shyam; Hazel, Tom; Johe, Karl; Bullock, M Ross
Abstract: INTRODUCTION: Human neural stem cells (hNSCs) transplantation in several experimental brain injury models has established their therapeutic potential. However, such a promising cell replacement strategy has not been studied in experimental acute subdural hematoma according to current literature. Aside from emergent surgical decompression through evacuation of hematoma and rehabilitation, there are no proven effective treatments exist to aid neurological recovery. Therefore, we aimed to test the feasibility of hNSCs transplantation in rat ASDH decompression model for functional recovery using 2 clinically relevant transplantation approaches. METHODS: Athymic rats were randomized into ASDH and control groups respectively (7-10/group). The ASDH rats then underwent craniotomy for hematoma evacuation mimicking emergent decompression. One week following injury, the rats were subjected to 2 different hNSCs transplantation approaches 1) direct stereotaxic injection at proximal motor area 2) Onlay of hNSC embedded collagen matrix based dural graft (DuraGen) over affected cortical surface (mimicking duroplasty). Behavioral testing was carried out to assess motor function recovery following ASDH induction and decompression utilizing rotarod method. The rats were then sacrificed at 4 and 8 wk timepoint for histoimmunochemistry analysis. RESULTS: There were robust engraftment of the hNSCs in ASDH group at 4 and 8 wk following transplantation. The hNSCs extended neuritis-like projections toward deep parenchyma, resembling neural dendrites. In comparison the direct in situ transplantation group had greater engraftment than the dural draft embedding approach. Immunochemistry with douclecortin, NeuN, and GFAP at 8 wk after transplantation showed that the transplanted hNSCs remained as immature neurons and did not differentiate toward to glial cell lines. In regards to motor recovery, the hNSCs transplant group showed steady increased in motor function up to 4 wk after transplantation. The latency to fall from rotarod was significantly higher in the hNSCs transplantation group compared to control from 2 wk onward post transplantation. CONCLUSION: This is the first study demonstrates robust engraftment of hNSCs via 2 different clinically relevant transplantation approaches in ASDH following craniotomy. There were impressive functional recovery demonstrated in the hNSCs group. The results from this study is promising as an additional neurosurgical intervention to treat functional deficit as a result of ASDH in future.